Liver Support With Albumin Dialysis Reduces Hepatitis C Virus Viremia and Facilitates Antiviral Treatment of Severe Hepatitis C Virus Recurrence After Liver Transplantation. Issue 2 (1st March 2016) - Ibáñez‐Samaniego, Luis; Catalina, María‐Vega; Rincón, Diego; Lo Iacono, Oreste; Fernández, Ainhoa; Clemente, Gerardo; Bañares, Rafael; Vaquero, Javier; Salcedo, Magdalena
Abstract: Patients with severe hepatitis C virus (HCV) recurrence after liver transplantation (LT) present an ominous prognosis, rarely achieving sustained virological response (SVR). Dialysis procedures may transiently decrease the HCV viral load, but the effect of albumin dialysis is currently unknown. Here, we evaluated the impact of albumin dialysis using the Molecular Adsorbent Recirculating System (MARS) used as a co‐adjuvant antiviral treatment for severe HCV recurrence after LT. Thirteen patients (11 males, median age 48 years) with fibrosing cholestatic hepatitis or METAVIR fibrosis score ≥ F3 with severe portal hypertension underwent three consecutive MARS sessions. Antiviral therapy was initiated in 11 patients within 24 h after the MARS sessions. A contemporary cohort of seven patients who did not follow the MARS protocol is shown for comparison. MARS treatment resulted in consistent decreases of viral load from 7.59 log10 IU/mL [6.15–8.90] to 6.79 log10 IU/mL [5.18–7.84] ( P =  0.003) as well as in decreases of serum bilirubin, gamma‐glutamyl transpeptidase, alanine aminotransferase and aspartate aminotransferase (all P <  0.05). The overall rate of SVR was 0% in the Control group and 54.6% in patients initiating antiviral therapy within 24 h after MARS. Survival at 1 and 3 years was, respectively, 93% and 70% in patients undergoing MARS, compared with 29% and 14% in the Control group ( P =  0.001). No major adverse events related to MARS treatment were observed. In conclusion, the use of MARS may facilitate the achievement of SVR and improve the prognosis of patients with severe HCV‐recurrence after LT by reducing viral load and improving liver function prior to antiviral therapy.